ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nisa, Thoyibatun (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2020)
This study analyzes the company's financial performance using profitability ratios, and liquidity ratio in mining sector companies listed on the Indonesia Stock Exchange. The sample in this study were 3 mining companies, namely PT Adaro Energi Tbk, PT Aneka Tambang Persero Tbk, and PT Ratu Prabu Energi Tbk which were listed on the Indonesia Stock Exchange. According to Ross Stephen a company's financial performance can be assessed using several financial analysis techniques, namely: financial ratio analysis, common size analysis, horizontal/trend analysis, analysis of sources and uses of cash, and discriminant analysis/Z-Score. The analysis technique used in the analysis is the financial ratio analysis technique. The data used in this research is secondary data. The results of this study indicate the overall profitability ratios and liquidity ratios of PT Adaro Energi Tbk, PT Aneka Tambang Persero Tbk, and PT Ratu Prabu Energi Tbk. Keywords: Profitability, Liquidity, and Financial Performance.